Judicialização da saúde: limite do judiciário no fornecimento dos medicamentos de alto custo - Martins, Paloma da Silveira (My University, 2023)
This academic work had as its theme the judicialization of health in cases of high-cost medicines, and its research problem is the following: what is the limit of the judiciary to guarantee the fundamental right to health? To respond to this problem, the hypothetical-deductive method of approach was used, in order to verify the hypotheses that were pointed out, in which case studies were carried out based on jurisprudence and bibliographic content. It analyzed in a jurisprudential, doctrinal and normative manner the decisions regarding high-cost drugs. The general hypothesis is that it is possible to have no limits to the fundamental right of health. The work was divided into three chapters, where the first dealt with the fundamental right to health, the second with the limits of the judiciary to the fundamental right to health, the third with the judicialization of health as a fundamental guarantee. The present research, by using all the previously mentioned means, concluded that there is a limit to the right to health, mainly with regard to the Judiciary and based on the criteria established in Theme 106 of the STF, where the power public has the obligation to supply medicines not incorporated in normative acts of the SUS and Theme 500, of the STF, where the State has the duty to supply medicines without registration in ANVISA, provided that there is an application for registration of the medicine in Brazil (with exception of medicines for rare diseases), registration of the medicine in agencies abroad and the lack of medicine that can replace it with registration in Brazil. [resumo fornecido pelo autor]
Este trabalho acadêmico teve como tema a judicialização da saúde nos casos de medicamentos de alto custo, sendo seu problema de pesquisa o seguinte: qual o limite do judiciário, para a garantir o direito fundamental à saúde? Para responder a este problema, foi utilizado o método de abordagem hipotético-dedutivo, a fim de verificar as hipóteses que foram apontadas, no qual realizou estudo de casos a partir de jurisprudências e conteúdo bibliográfico. Analisou de forma jurisprudencial, doutrinária e normativa as decisões em relação aos medicamentos de alto custo. A hipótese geral é de que é possível não ter limites ao direito fundamental da saúde. O trabalho foi dividido em três capítulos, onde o primeiro tratou do direito fundamental à saúde, o segundo dos limites do judiciário ao direito fundamental à saúde, o terceiro da judicialização da saúde como garantia fundamental. A presente pesquisa, ao utilizar se de todos os meios anteriormente citados, concluiu que existe um limite no direito à saúde, principalmente no que tange ao Poder Judiciário e que se tenham como base os critérios estabelecidos no Tema 106 do STF, onde o poder público tem a obrigatoriedade de fornecer medicamentos não incorporados em atos normativos do SUS e o Tema 500, do STF, onde o Estado tem o dever de fornecer medicamentos sem registro na ANVISA, desde que tenha existência de pedido de registro do medicamento no Brasil (com exceção de medicamentos com doenças raras), registro do medicamento em agências no exterior e a inexistência de medicamento que possa substitui-lo com registro no Brasil. [resumo fornecido pelo autor]
Keywords: Direito à saúde; Direitos fundamentais